2009
DOI: 10.1099/vir.0.009688-0
|View full text |Cite
|
Sign up to set email alerts
|

Fusion protein is the main determinant of metapneumovirus host tropism

Abstract: Human metapneumovirus (HMPV) and avian metapneumovirus subgroup C (AMPV-C) infect humans and birds, respectively. This study confirmed the difference in host range in turkey poults, and analysed the contribution of the individual metapneumovirus genes to host range in an in vitro cell-culture model. Mammalian Vero-118 cells supported replication of both HMPV and AMPV-C in contrast to avian quail fibroblast (QT6) cells in which only AMPV-C replicated to high titres. Inoculation of Vero-118 and QT6 cells with re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 43 publications
0
15
0
1
Order By: Relevance
“…In cell culture, HMPV expressing only F (HMPVΔGΔSH) binds to the cell surface with the same efficiency as wild type virus [61]. Moreover, HMPV F confers species specificity of infection, as F was found to be primarily responsible for the difference in the ability of AMPV-C and HMPV to infect quail fibroblast (QT6) cells [62]. Further, the F2 subunit (and not the G protein) of both hRSV [38] and HMPV [62] has been shown to confer species-specific infection of cells.…”
Section: Hmpv Binding: Identifying the Doormentioning
confidence: 99%
See 1 more Smart Citation
“…In cell culture, HMPV expressing only F (HMPVΔGΔSH) binds to the cell surface with the same efficiency as wild type virus [61]. Moreover, HMPV F confers species specificity of infection, as F was found to be primarily responsible for the difference in the ability of AMPV-C and HMPV to infect quail fibroblast (QT6) cells [62]. Further, the F2 subunit (and not the G protein) of both hRSV [38] and HMPV [62] has been shown to confer species-specific infection of cells.…”
Section: Hmpv Binding: Identifying the Doormentioning
confidence: 99%
“…Moreover, HMPV F confers species specificity of infection, as F was found to be primarily responsible for the difference in the ability of AMPV-C and HMPV to infect quail fibroblast (QT6) cells [62]. Further, the F2 subunit (and not the G protein) of both hRSV [38] and HMPV [62] has been shown to confer species-specific infection of cells. This evidence strongly indicated that HMPV F interacts with cell surface receptors, and both protein and carbohydrate receptors for HMPV F have been discovered.…”
Section: Hmpv Binding: Identifying the Doormentioning
confidence: 99%
“…As for most paramyxoviruses, the trigger that leads to the membrane fusion event remains unknown, although it is tempting to speculate that binding to integrin ␣v␤1 may provide such a trigger (47). By generating chimeric viruses between HMPV and AMPV, it has been shown that the F protein is an important determinant of metapneumovirus host range (57).…”
Section: Fig 2 Genomic Maps Of Hmpv and Rsvmentioning
confidence: 99%
“…F protein is synthesized as a precursor, and its activation requires cleavage by host cell protease (37,38). Vector-expressed or mammalian cell-expressed F protein can induce high levels of neutralizing antibodies and produce moderate resistance to the replication of intranasally administered challenge virus, suggesting that F protein is one of the major antigens that induce protection against hMPV infection (4,11,12).…”
Section: Discussionmentioning
confidence: 99%